2008
DOI: 10.1007/s10096-008-0674-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel macroarray-based method of Corynebacterium diphtheriae genotyping: evaluation in a field study in Belarus

Abstract: In this study, we evaluated a novel macroarray-based spoligotyping method for Corynebacterium diphtheriae strain typing. A total of 20 C. diphtheriae biotype gravis toxigenic isolates collected in Belarus from suspected foci of diphtheria infection (diphtheria cases, carriers, or contacts) were subjected to DNA fingerprinting. All strains had an identical ribotyping profile that was identified as ribotype 'Rossija' by comparison with the international ribotype database at the Institut Pasteur of Paris. A spoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…Louwen et al thus established that not only the spacer variation of the CRISPR array but also single nucleotide polymorphisms (SNPs) of the cas genes in C. jejuni are useful for typing purposes (30). Likewise, in Corynebacterium diphtheriae, the CRISPR-Cas systems (type I-E and type II-C) were found to be useful for typing purposes (32,33). Remarkably, spoligotyping, a technique making use of sequence information contained within the CRISPR spacers, was found to provide enhanced discriminatory power in C. diphtheriae compared to pulsed-field gel electrophoresis (PFGE), random amplification of polymorphic DNA (RAPD), and AFLP analyses (33).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Louwen et al thus established that not only the spacer variation of the CRISPR array but also single nucleotide polymorphisms (SNPs) of the cas genes in C. jejuni are useful for typing purposes (30). Likewise, in Corynebacterium diphtheriae, the CRISPR-Cas systems (type I-E and type II-C) were found to be useful for typing purposes (32,33). Remarkably, spoligotyping, a technique making use of sequence information contained within the CRISPR spacers, was found to provide enhanced discriminatory power in C. diphtheriae compared to pulsed-field gel electrophoresis (PFGE), random amplification of polymorphic DNA (RAPD), and AFLP analyses (33).…”
Section: Figmentioning
confidence: 99%
“…Likewise, in Corynebacterium diphtheriae, the CRISPR-Cas systems (type I-E and type II-C) were found to be useful for typing purposes (32,33). Remarkably, spoligotyping, a technique making use of sequence information contained within the CRISPR spacers, was found to provide enhanced discriminatory power in C. diphtheriae compared to pulsed-field gel electrophoresis (PFGE), random amplification of polymorphic DNA (RAPD), and AFLP analyses (33). Furthermore, spoligotyping had discriminatory power for subtyping of Legionella pneumophila strains and enabled the identification of environmental sources that caused clinical outbreaks (34).…”
Section: Figmentioning
confidence: 99%
“…The diversity of CRISPR spacer sequences has been used as the basis for genotyping several pathogens, and these spoligotyping methods have demonstrated comparable in index of discrimination values to those of the gold standard genotyping methods, such as PFGE, multilocus sequence typing (MLST), amplified fragment length polymorphism (AFLP), or multiple-locus variable-number tandem-repeat analysis (MLVA), demonstrating the usefulness of this method for typing purposes (14,16,17,20). In this study, using the genome of the Paris CIP107629 reference strain, we explored the diversity of CRISPR spacers and developed a spoligotyping tool that was able to discriminate L. pneumophila ST1/Paris pulsotype isolates that were formerly undistinguishable with PFGE and SBT (5).…”
Section: Discussionmentioning
confidence: 99%
“…ST1/Paris pulsotype isolates have also been detected in clinical and environmental samples from several other countries around the world, including Switzerland, Italy, Spain, Sweden, the United States, Japan, Senegal, and Canada (1, 4). The high isolation rate of this strain in clinical and environmental samples makes it difficult, and frequently impossible, to identify the environmental source of an infection during epidemiological investigations.Recent studies have demonstrated the value of using the diversity of CRISPR spacers as genotyping markers for several pathogenic agents, and spoligotyping tools have been successfully developed for this purpose (14,17,19,20). The aim of this study was to design the first spoligotyping tool for subtyping L. pneumophila ST1/Paris pulsotype isolates and to evaluate its performance and efficiency on a collection of clinical and environmental isolates from France.…”
mentioning
confidence: 99%
See 1 more Smart Citation